English Physiological, immunological and microbial effects of soybean bioactive peptides and vitamin E supplementing to broiler diet - Sa’adoon , Waleed Hailan; Abbas, Rabia Jaddoa (Acta Scientiarum. Animal Sciences, 2023)
The physiological, immunological, and microbiological traits of 180 Ross-308 broiler chickens were examined in relation to supplementary soybean bioactive peptide (SBP) levels and vitamin E. Group 1 was the control group, Groups 2, 3, and 4 were given a basal diet along with 2.5, 5, and 7.5 g SBP kg-1 of diet, respectively, and Group 5 was given a basal diet together with 250 mg of vitamin E kg-1 of diet. An improvement in the globulin, albumin-to-globulin ratio, total antioxidant activity (except 7.5 g), SOD, and GSH-PX (except 7.5 g) activities in SBP treatment groups compared to the control. In comparison with control, feeding SBP improved bursa index, IgA, and IgG concentrations in blood serum. Feed supplementation with 5 g SBP significantly increased relative weight of spleen and IgM concentrations. Feeding SBP increased lactic acid bacteria in the ileum and caecum while decreasing E. coli counts in the ileum as compared with control. None of the selected serum biochemical indices, immune-related parameters, and total bacterial count were statistically different between the vitamin E group and the control. Therefore, 5 and 7.5 g of SBP kg-1 in a broiler diet was able to boost antioxidant status, antibacterial activity, and birds’ immune response.